2014
DOI: 10.1590/s1516-8913201402132
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of fibrinolytic protease production from Bacillus subtilis I-2 using agro-residues

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 26 publications
1
32
1
1
Order By: Relevance
“…This is a likely pointer towards the role, though minor in magnitude, played by the carbon source in enhancing the FEA in the media. In our study, we found that a nitrogen source played a major role played in enhancing the fibrinolytic activity in the media and was in good agreement with the results reported by Bajaj et al (2014). We determined that there is no appreciable change in activity as the inoculum increases from 1% (v/v) to 5% (v/v) and a further increase to 7% (v/v) inoculum volume led to reduced activity levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is a likely pointer towards the role, though minor in magnitude, played by the carbon source in enhancing the FEA in the media. In our study, we found that a nitrogen source played a major role played in enhancing the fibrinolytic activity in the media and was in good agreement with the results reported by Bajaj et al (2014). We determined that there is no appreciable change in activity as the inoculum increases from 1% (v/v) to 5% (v/v) and a further increase to 7% (v/v) inoculum volume led to reduced activity levels.…”
Section: Discussionsupporting
confidence: 91%
“…Microbial production of plasmin-like protease from microorganisms such as Bacillus sp. (Afifah et al, 2014;Bajaj et al, 2014;Gu et al, 2009;Liu et al, 2005) and Petasites japonicas (Kim et al, 2015), etc., have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrin plays a vital role in health and healing; however, formation of inappropriate clot especially under certain pathophysiological conditions in the body is a major risk factor for heart disorders (Bajaj et al , 2014. Homoeostasis of formation and dissolution of fibrin maintain appropriate viscosity in the vascular system.…”
Section: Fibrinolytic Proteases As Thrombolytic Agentsmentioning
confidence: 99%
“…Enzyme-based industrial processes are much more environmentally safer than the traditional chemical ones and involve less emissions (Sheldon et al 2007). But considering that enzymes are the biological molecules which are largely designed (by nature) to function under ambient conditions in the living systems, may not suit well for relatively hostile industrial process conditions (Bajaj et al 2014). Therefore, discovery of sturdy enzymes that are capable of functioning under industrial processes has gained considerable research impetus in recent years (Sharma and Bajaj 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lately, many studies have applied this technique for the production of industrially important enzymes such as cyanide degradation ability of bacterial consortium was enhanced by the statistical methods of optimization [13]. Similarly, culture conditions have been optimized for enhanced production of protease from Bacillus subtilis [14]. RSM being less laborious and timeconsuming has been applied successfully in biotechnological processes to decreases the number of experimental trials [15].…”
Section: Introductionmentioning
confidence: 99%